“Caracterización de la mosca de la fruta en el cantón Pangua parroquia Moraspungo provincia de Cotopaxi 2020.” - Vivanco Sopa, Diana Marisol (2020)
This research project is located in Pangua Canton, Moraspungo Parish, Province of Cotopaxi, at an altitude ranging from 100 to 3,600 meters above sea level to characterize the types of fruit flies (Anastrepha spp. And Ceratitis w) present in the canton and in this way to find an alternative for the control and management of the fly population. The main hosts related to the Fruit Fly are papaya, guava, soursop, orange, lime, grapefruit, "achotillo", sweet pepper, "guaba", "araza", mango, mandarin. The Moraspungo parish is defined as a highly fruit-growing area, a monitoring route was established that goes from Guapara, Moraspungo, and Palo Seco, in this way 38 georeferenced traps with GPS were installed at a distance of 1 km between each trap. The “Multilure” type traps baited with 2 pellets ("tolura" yeast tablets) and 250 cc of water were used for each trap. We placed them on the different host trees related to this insect during a period of two months. The specimens were carried out every seven days, and the bait was changed every 14 days, keeping a record of the population and identification of the genera and species of flies. The following species were identified in the "Agrocalidad" Entomology laboratory: Anastrepha (A. sp, A. striata, A. faterculus, A. oblique, A. serpentina, A. atrox, A. distincta). In the study area, the presence of Anastrepha faterculus was mostly detected. Ceratitis capitata was not found in Moraspungo during the investigation period. The efficiency of the food bait (YeastTolure) was measured based on the Fly / Trap / Day capture index, it is clear that food attractants are an important part of the integrated management of fruit flies.